Pelestarian Cerita Rakyat Kabupaten Melawi dan Relevansinya dengan Pembelajaran Bahasa Indonesia di Sekolah Dasar - Mastiah, Mastiah; Albar, Joni (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: Melawi Regency, West Kalimantan, possesses a rich cultural heritage with local wisdom reflected in its folklore. However, with the passage of time, this folklore is at risk of extinction due to the lack of attention from the younger generation. This study aims to explore the preservation of folklore in Melawi Regency and its relevance to Indonesian language learning in elementary schools. A descriptive qualitative method with an inventory model approach was used to collect and document folklore from various villages in Melawi. A total of 11 folk tales were identified and analyzed for integration into the curriculum. The results of the study show that folklore contains important moral, ethical, and social values that are crucial for character education. Additionally, folklore also helps to strengthen both local and national cultural identities. By integrating folklore into Indonesian language learning in elementary schools, cultural preservation can be effectively achieved, while simultaneously enhancing students' learning experiences.Keywords: folklore preservation, local wisdom, Indonesian language learning.Abstrak: Kabupaten Melawi, Kalimantan Barat, memiliki warisan budaya yang kaya dengan kearifan lokal yang tercermin dalam cerita rakyat. Namun, dengan perkembangan zaman, cerita rakyat ini terancam punah karena kurangnya perhatian dari generasi muda. Penelitian ini bertujuan untuk mengeksplorasi pelestarian cerita rakyat di Kabupaten Melawi dan relevansinya dengan pembelajaran Bahasa Indonesia di sekolah dasar. Metode kualitatif deskriptif dengan pendekatan model inventarisasi digunakan untuk mengumpulkan dan mendokumentasikan cerita rakyat dari berbagai desa di Melawi. Sebanyak 11 cerita rakyat berhasil diidentifikasi dan dianalisis untuk diintegrasikan dalam kurikulum pembelajaran. Hasil penelitian menunjukkan bahwa cerita rakyat memiliki nilai moral, etika, dan sosial yang penting untuk pendidikan karakter siswa. Selain itu, cerita rakyat juga membantu memperkuat identitas budaya lokal dan nasional. Dengan mengintegrasikan cerita rakyat dalam pembelajaran Bahasa Indonesia di sekolah dasar, pelestarian budaya dapat dilakukan secara efektif, sekaligus meningkatkan pengalaman belajar siswa.Kata Kunci: pelestarian cerita rakyat, kearifan lokal, pembelajaran Bahasa Indonesia.